2010
DOI: 10.1080/02671520903045566
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the assessment of citizenship

Abstract: This paper draws on some of the findings from a research study which examined the current structure of assessment for citizenship in secondary education in England and considers the rationale for the assessment of citizenship. The research included an empirical evaluation of citizenship assessment from the perspective of the key user groups, teachers and pupils and comprised a mixed-method approach. A questionnaire survey was sent to teachers and pupils in secondary schools across England and interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Following on from this is the specific issue of assessment which illustrates how PSHE education can be devalued because it is often not formally assessed as other 'academic' subjects are (see also Richardson, 2010 for a comparison with the assessment of citizenship education). As one PSHE education lead pointed out:…”
mentioning
confidence: 99%
“…Following on from this is the specific issue of assessment which illustrates how PSHE education can be devalued because it is often not formally assessed as other 'academic' subjects are (see also Richardson, 2010 for a comparison with the assessment of citizenship education). As one PSHE education lead pointed out:…”
mentioning
confidence: 99%
“…Citizenship is not a compulsory part of the primary curriculum and at secondary school its content is dominated by legislation/law, making it difficult to explore the subject creatively. As previous research has found (see Richardson, 2010), the lack of coherent assessment of the subject means its value is diminished in the eyes of students and teachers.…”
Section: Educating For Citizenshipmentioning
confidence: 89%
“…In this paper we consider assessment as a special type of evaluation, and consider different instruments as modes of assessment (Dochy, 2001). To date, knowledge on student assessment in citizenship education is still preliminary, and no one way of assessing students' learning in citizenship education appears most suitable (Kerr, Keating, & Ireland, 2009;Richardson, 2010). The advantages and disadvantages of different modes of assessing students' citizenship competences are associated with the specific goals strived for.…”
Section: Introductionmentioning
confidence: 99%